The effect of Lactobacillus plantarum 1A-2 and 1BL-2 inoculant on the quality of napier grass silage - SHANTI RATNAKOMALA; RONI RIDWAN; GINA KARTINA; YANTYATI WIDYASTUTI (Society for Indonesian Biodiversity, 2006)
Ensiling is one solution to handle lack of forage at dry and wet season in tropical area. Napier grass (Pennisetum purpureum) is a popular crop conserved as silage, regarded with a relatively high dry matter (DM) content and adequate water soluble carbohydrates for fermentation to lactic acid. The aim of this study was to determine the effect of adding lactic acid bacteria inoculants to Napier grass at ensiling on the quality of silage. Two strain lactic acid bacteria inoculants Lactobacillus plantarum 1A-2 and 1BL-2 were added to the grass at different variation of inoculants , single or mix strain (0%, 0.1%, 0.3%, 0.5%, and 1%) with 3% of rice brand as additive, and incubated for 30 days. The 1A-2 inoculants treatment lowered the pH between 3.67 to 4.18 and increased the lactate level of the grass silage 0.3 to 0.34 mg mL-1 compared with the control and other treatments. The parameters for destruction is under 5% and DM loss was considerably lower in single inoculants 1BL-2 (0.01-3.97%) and 1A-2 (0.31-5.18%). Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: silage, fermentation, potential microorganism, lactic acid bacteria